Lumboperitoneal Shunt - A Simple Answer to Idiopathic Intracranial Hypertension (Journal of Medicine, 2012)
Idiopathic Intracranial Hypertension commonly can present in young women. It is a relatively common disorder but unfortunately under diagnosed. Surgery can be an option of treatment for these patients. Here we report a can not a young girl presenting with IIH, successfully treated by a shunt surgery. DOI: http://dx.doi.org/10.3329/jom.v13i1.10081 JOM 2012; 13(1): 82-84